ESTIMATION OF CARBON RESERVED IN MANGROVE FOREST OF SUNGAI APIT DISTRICT, SIAK REGENCY, RIAU PROVINCE - Dewi, Delviana; Efriyeldi, Efriyeldi; Amin, Bintal (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2021)
Mangrove forests can absorb and store carbon in large quantities and for a long time, so they can play a role in mitigating climate change. This research was conducted in February 2021 on the Mangrove Ecosystem in the Sungai Bersejarah Mangrove Tourism Area of ​​Kayu Ara Permai Village, aiming to identify species and analyze mangrove density, mangrove biomass and carbon content, CO2 uptake, as well as analyzing the relationship between mangrove density and biomass, carbon stock and CO2 uptake. This study uses a survey method, the measurement of mangrove biomass using the allometric equation method. The results of the highest average mangrove density, potential estimates of carbon stock and CO2 absorption are found on Transect 3 which shows an average mangrove density of 2166.66 ind/ha, mangrove carbon stock 91.9378 tons/ha and CO2 absorption of 336.5667 tons/ha. The largest soil organic carbon was found in transect 3, which was 384.15 tons/ha. Density does not have a strong relationship with biomass, mangrove carbon content and carbon sequestration. Mangrove density between transects showed a significant difference (p<0.05). Biomass, mangrove carbon and CO2 uptake between transects were not significantly different (p>0.05), while the estimated soil organic carbon stock was significantly different (p<0.05) between transects.